SOCIAL ADAPTATION OF INTERNATIONAL STUDENTS IN THE CONDITIONS OF TRAINING DURING COVID-19 PANDEMIC - І. Савка; С. Савка; Н. Войткевич (Bukovynian State Medical University, 2023)
Introduction. Social adaptation is an important part of adjustment of international students to training at educational establishments. Better academic achievements among international students are associated with the University membership and a high level of cross-cultural relations. All the components of social adaptation in the conditions of training during COVID-19 pandemic naturally have undergone substantial changes. It is also reflected on psychological state of students, since every country of residence introduced certain quarantine regulations at different times. Some of these regulations were rather strict including curfew and prohibition to leave the house. Under such conditions worries of parents concerning incidence of COVID-19 at home and the country of residence cannot be excluded, as well as intensification of nostalgia due to impossibility to cross the border and return home etc. Objective of our research was to study the main components forming social adaptation of international students in the conditions of quarantine caused by COVID-19. Materials and methods. Our study involved 220 junior students of the 1st-3rd years of training at Bukovinian State Medical University (BSMU). In order to obtain maximum objective and reliable results, the survey was anonymous and randomized involving every third student of a corresponding year of studies. The whole list of questions was arranged into one questionnaire. A student had to give a positive or negative answer. Social adaptation of international students was assessed by means of the Student Adaptation to College Questionnaire (SACQ) developed by Robert W. Baker and Bohdan Siryk (1989, 1994) with the author's changes and modifications. About 85% of students involved in the survey were from India, about 4% - from Ghana, the rest 11% of the students were from other countries of Asia, Europe, Africa and USA. Results. Under conditions of transfer to the distance learning under pandemic conditions due to COVID-19 the components of social adaptation of international students remain on rather high levels. Thus, the level of general social adaptation under the above conditions remained on the highest and high rates among 55% international learners of higher education, and the rate of social distancing and communication with other people was in 41,4% of foreigners. Nostalgia level was maximum among 55,5% of international students under quarantine conditions of studies, and the rates of social adaptation to the environment remained on the highest levels practically among 80% of respondents. At the same time, direct interrelations of a moderate and strong levels are found between general social adaptation and social distancing with other people, nostalgia, social adaptation to the environment, between social distancing with other people and nostalgia, social distancing and social adaptation to the environment, and between nostalgia and social adaptation to the environment. Conclusions. One of the important components for successful academic progress of international students is their social adaptation. At the same time, all the major components of social adaptation in the form of general social adaptation, social distancing and communication with other people, nostalgia and social adaptation to the environment remain on the highest or rather high levels among the prevailing majority of international applicants of higher medical education under conditions of new forms of training during pandemic caused by COVID-19.